Indicators of nutritional status in restricting-type anorexia nervosa patients: a 1-year follow-up study - Nova, Esther; Lopez-Vidriero, Irene; Varela, Pilar; Toro, Olga; Casas, José; Marcos, Ascensión (Clinical nutrition (Edinburgh, Scotland), 2004)
Background & aim: Despite severely reduced intakes, anorexia nervosa (AN) patients seem to maintain serum biochemical parameters within the safe limit. The aim of this study was to assess the evolution of some traditional serum biochemical indicators of nutritional status in a 1-year follow-up of patients with restricting-type AN. Methods: 14 adolescent female patients were studied at four different time points: (1) on hospital admission (t0), (2) 1 month later (t1), (3) 6 months after admission (t6) and (4) 12 months after admission (t12). At each time point serum albumin, prealbumin, retinol-binding protein, transferrin, complement factors C3 and C4, zinc and iron status were analysed. 15 healthy adolescents formed the control group. Results: Among the liver-synthesised proteins, a significant time effect was only demonstrated on transferrin and C3 and C4 (ANOVA, P<0.05). Transferrin level in patients on admission was lower than in controls, increased significantly during the first month and showed an opposite pattern in subjects gaining and non-gaining weight between t1 and t12, decreasing only in the group failing to gain further weight. C3 and C4 decreased significantly in t12. Changes in ferritin and zinc showed significant negative correlations with changes in anthropometrical parameters. Conclusions: The changes in transferrin, C3 and C4 levels during the out-patient treatment reveal an increased risk of relapses after 1 year since hospital admission. Ferritin and zinc levels seem to be affected by the nutrient requirements for anabolic processes during nutritional recovery.